[Violence in children ; Ifugao of the heart ; Gary V. [videorecording] - Lazaro, Cheche (Quezon City Probe Productions)
Talks about covert violence; importance of mother to tongue by the Ifugaos; transformation of Gary Valenciano in the performance of his songs from an ordinary to a Christian one.
Violence in children (23 min.) -- Ifugao in the heart (14 min.) -- Gary V. (13 min.)
VHS.
Keywords: Valenciano, Gary; Summer Institute of Linguistics; Children and violence -- Philippines; Philippine language; Tumali language; Violence in children